﻿Reassessment of the type locality of Euptychia stigmatica Godman, 1905, with the description of two new sibling species from Amazonia (Lepidoptera, Nymphalidae, Satyrinae, Satyrini) - Shinichi Nakahara; Kaylin Kleckner; Eduardo P. Barbosa; Giselle M. Lourenço; Mirna M. Casagrande; Keith R. Willmott; André V. L. Freitas (ZooKeys, 2023)
A brief historical review regarding the type locality of Euptychia stigmatica Godman, 1905 was conducted, which suggests that its type locality is actually Rio de Janeiro, Brazil, rather than northeastern Argentina, as previously purported. Consequently, E. stigmatica and its senior synonym E. cyanites Butler, 1871, are regarded to be two species-group names representing a taxon in the euptychiine genus Caeruleuptychia Forster, 1964 known from the Brazilian Atlantic Forest. A lectotype is designated for E. cyanites. Additionally, two closely related species are named and described using an integrative approach with morphological and molecular evidence. Caeruleuptychia harrisi Nakahara & Freitas, sp. nov. and C. aemulatio Nakahara & Willmott, sp. nov. both occur in Amazonia and COI barcode data recovered these taxa as part of the caerulea clade of Caeruleuptychia.